Effects of Game Situation-Dependent Emotions on Sport Spectators’ Food Craving - Chang, Yonghwan (Frontiers in Psychology, 2021)
This study sought to challenge prevalent accounts of emotional eating by exploring the effects of situation-dependent emotions on consumers’ food craving. Four specific game situations in the context of spectator sports, each corresponding to the four types of emotional coping (outcome-desire conflict, avoidance, fulfillment, and pursuit), were identified as follows: decisive victories, decisive losses, close victories, and close losses. By employing lab-based virtual reality spectatorship, Study 1 tested the causal effects of happiness (fulfillment), anger (conflict), sadness (conflict), fear (avoidance), and hope (pursuit) on food craving. Study 2 further designed fans’ previous association between emotions and eating as a moderating mechanism in the context of online sport viewership. The results of the two experiments supported the three theoretical principles of eating behavior, including the “food as fuel” principle of anger, the hedonic eating principle of happiness, and the self-regulation principle of hope. However, the results rejected the escape awareness principle of sadness and fear. The study concludes with a discussion of context-dependent emotional positioning and intervention strategies for marketers, health professionals, and policy makers.